Pengaruh Kompensasi, Lingkungan Kerja Non Fisik, Dan Pengembangan Karir Terhadap Retensi Karyawan Pada PT BPRS Madina Mandiri Sejahtera - Pradita Nindya Aryandha; Deffani Aksan (Universitas PGRI Yogyakarta, 2024)
This study aims to determine the effect of compensation, non-physical work environment, and career development on employee retention. This research was conducted at PT BPRS Madina Mandiri Sejahtera in 2022. This research is a quantitative study with 40 respondents using a sampling technique, namely the saturated sampling technique. Data collection technique is done by distributing questionnaires. The analysis technique used is multiple linear regression analysis. The results showed that partially compensation had a positive and significant effect on employee retention. The non-physical work environment has a positive and significant effect on employee retention. Career development has no positive and significant effect on employee retention. The results of the study simultaneously compensation, non-physical work environment, and career development on employee retention.